Deep brain stimulation versus vagus nerve stimulation for the motor function of poststroke hemiplegia: study protocol for a multicentre randomised controlled trial - Bin Liu; Xinguang Yu; Qing Chang; Di Liu; Yanyang Zhang; Junpeng Xu; Haonan Yang; Zhiqi Mao; Guosong Shang; Shuzhen Liu; Zhebin Feng; Chen Yuhan (BMJ Open)
Introduction Deep brain stimulation (DBS) and vagus nerve stimulation (VNS) can improve motor function in patients with poststroke hemiplegia. No comparison study exists.Methods and analysis This is a randomised, double-blind, controlled clinical trial involving 64 patients who had their first stroke at least 6 months ago and are experiencing poststroke limb dysfunction. These patients must receive necessary support at home and consent to participate. The aim is to evaluate the effectiveness and safety of DBS and VNS therapies. Patients are excluded if they have implantable devices that are sensitive to electrical currents, severe abnormalities in their lower limbs or are unable to comply with the trial procedures. The study has two parallel, distinct treatment arms: the Stimulation Group and the Sham Group. Initially, the Stimulation Group will undergo immediate electrical stimulation postsurgery, while the Sham Group will receive non-stimulation 1 month later. After 3 months, these groups will swap treatments, with the Stimulation Group discontinuing stimulation and the Sham Group initiating stimulation. Six months later, both groups will resume active stimulation. Our primary outcomes will meticulously assess motor function improvements, using the Fugl-Meyer Assessment, and safety, monitored by tracking adverse reaction rates. Furthermore, we will gain a comprehensive view of patient outcomes by evaluating secondary measures, including clinical improvement (National Institutes of Health Stroke Scale), surgical complications/side effects, quality of life (36-item Short Form Questionnaire) and mental health status (Hamilton Anxiety Rating Scale/Hamilton Depression Rating Scale). To ensure a thorough understanding of the long-term effects, we will conduct follow-ups at 9 and 12 months postsurgery, with additional long-term assessments at 15 and 18 months. These follow-ups will assess the sustained performance and durability of the treatment effects. The statistical analysis will uncover the optimal treatment strategy for poststroke hemiplegia, providing valuable insights for clinicians and patients alike.Ethics and dissemination This study was reviewed and approved by the Ethical Committee of Chinese PLA General Hospital (S2022-789-01). The findings will be submitted for publication in peer-reviewed journals with online accessibility, ensuring adherence to the conventional scientific publishing process while clarifying how the research outcomes will be disseminated and accessed.Trial registration number NCT06121947.